Two centuries of sponges (phylum Porifera) taxonomic studies in Indonesia (1820–2021): checklist and bibliography - Putra, Singgih Afifa; Ambo-Rappe, Rohani; Jompa, Jamaluddin; Voogd, Nicole J. De (Zootaxa, 2023)
Sponges in Indonesia have been studied since the 19th century during several historical expeditions and international collaborations. Hundreds of new species were reported from various locations, e.g., Ambon, Ternate, Sulawesi, Aru, and Kei Islands. This study aimed to create a sponge (Porifera: Calcarea, Demospongiae, Hexactinellida, and Homoscleromorpha) species checklist from Indonesia based on World Porifera Database. With a total of 731 species, our checklist comprises approximately 45 species of Calcarea, 566 species of Demospongiae, 115 species of Hexactinellida, and five species of Homoscleromorpha. The number of species are recorded from 12 marine ecoregions across the Indonesian Archipelago and freshwater habitats (Spongillida) between 1820–2021. The species composition indicates higher regional endemism or poorly studied since no other report after the original description. However, several marine ecoregions of Indonesia remain highly overlooked (e.g., Northeast Sulawesi, Papua, Southern Java, Western Sumatra), including freshwater habitats. Therefore, a taxonomic biodiversity baseline study, particularly on Porifera, is necessary to better understand the aquatic and marine biodiversity in the Indonesia Archipelago.